Unburied versus buried wires for fixation of pediatric lateral condyle distal humeral fractures: A meta-analysis. Issue 34 (August 2017) - Qin, Ya-Fei; Li, Zhi-Jun; Li, Cheng-Kai; Bai, Shu-Cai; Li, Hui
Abstract : Abstract: Open reduction and internal fixation with Kirschner (K) wires has been reported as an efficient and convenient technique for pediatric lateral condyle distal humeral fractures. However, no single study has been large enough to definitively determine whether the K-wires should be buried or unburied. Therefore, we performed a meta-analysis pooling the results from several clinical trials to compare the outcome of using buried versus unburied K-wires. Potential academic articles were identified from the Cochrane Library, Medline (1966–2017.3), PubMed (1966–2017.3), Embase (1980–2017.3), ScienceDirect (1985–2017.3), and other databases. Gray studies were identified from the references of included literature reports. RevMan 5.1 was used to analyze the pooling of data. Nonrandomized controlled trials were included in this meta-analysis. There was a significant difference in the duration of wires in situ (MD = −13.28, 95% confidence interval: −16.42 to −10.14, P  < .00001). No significant differences were found regarding infection, superficial infection, total complications, delayed union, or reoperation. Unburied K-wire fixation for treatment of lateral condyle distal humeral fractures in children does not increase the total infection rate, superficial infection, reoperation rate, or complications. However, unburied K-wire fixation is of benefit for early extraction and impartial cost savings.